Development of Chernobyl's Power Plant capability through prism of project management methodology - Bushuyev, Sergey; Medintsov, Volodymyr; Sharovara, Elena (КНУБА, 2013)
With stopping at 2000 of power units of Chornobyl Nuclear Power Plant (ChNPP) problems of Chornobyl did not finished, they only had entered into a new no less responsible phase. Without experience in area of removal from exploitation of nuclear energy objects and building of objects similar to erected above an object " Shelter" to protective building, without the project of removal from exploitation of ChNPP, that under right had ratified 5years before the stop of the Plant, without the fund of financing of removal from exploitation of power units, ChNPP collective fulfills obligations taken by Ukraine before the world community on elimination of consequences of nuclear catastrophe of 1986. This activity demanded reorganization of organization, revision of basic functions and tasks, mastering of new, earlier not demanded on the ChNPP, fields of knowledge. The Project Management methodology became one of the bases of development capability for performance of the Ch NPP.
Keywords: diversification; unique experience; management of knowledge; innovations; projectoriented business management; project management methodology; benchmarking; the department project management